Application Of Blended Learning Models Combined With Mobile Games To Improve The Learning Outcomes Of Medical Biology Students - Dora Dayu Rahma Turista; Muhammad Zulhariadi; Zulkarnain Gazali (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Millennial generation is a term that is often used as a symbol of the rapid use of products by people today. The use of mobile phones connected to the internet is spread throughout the community. The material in medical biology courses is considered difficult by most students. The teacher tries to make improvements to the teaching and learning process by using learning models that are suitable for the millennial generation, that is blended learning model combined with mobile games. This study aims to determine the differences in learning outcomes of students who use the blended learning model combined with mobile games with the learning outcomes of students who use the direct learning model in medical biology courses. This research is an experimental quasy study that uses two sample groups, they are the experimental group and the control group. The results of the study were analyzed using Independent T test statistical analysis. Based on the research, there are significant differences in student learning outcomes using the blended learning model combined with mobile games with learning outcomes of students who use direct learning in medical biology courses, where students use blended learning models combined with mobile games have higher learning outcomes when compared with students who use the direct learning model.